Scanning electron microscopy of the attachment of Treponema pallidum to nerve cells in vitro. Issue 4 (August 1982) - Repesh, L A; Fitzgerald, T J; Oakes, S G; Pozos, R S
Abstract : Treponema pallidum (Nichols strain) was incubated with cultured nerve cells derived from rat embryos. Primary cultures were established from dorsal root ganglia, superior cervical ganglia, and spinal cord. Using phase contrast microscopy treponemes were seen to interact with the nerve cells in a similar manner to other cultured mammalian cells. Organisms began to attach within minutes after inoculation, actively motile organisms attached at the tip of one end, higher numbers of organisms attached with continued incubation, and attached organisms survived longer than unattached organisms. T pallidum attached both to nerve cell bodies and to neuronal processes of each of the three nerve cell cultures. As shown by scanning electron microscopy the mechanism of attachment was identical to that of cultured cells derived from rabbits testis, rat skeletal muscle, and human cervical carcinoma. There was no indentation or swelling of the cultured cell surface at the point of attachment, just a close physical proximity of organisms and cells. These techniques provide a biological means of studying the in-vitro detrimental influences of micro-organisms on nerve tissue.